2015
DOI: 10.1038/cdd.2015.84
|View full text |Cite
|
Sign up to set email alerts
|

Reduced mitochondrial Ca2+ transients stimulate autophagy in human fibroblasts carrying the 13514A>G mutation of the ND5 subunit of NADH dehydrogenase

Abstract: Mitochondrial disorders are a group of pathologies characterized by impairment of mitochondrial function mainly due to defects of the respiratory chain and consequent organellar energetics. This affects organs and tissues that require an efficient energy supply, such as brain and skeletal muscle. They are caused by mutations in both nuclear-and mitochondrial DNA (mtDNA)-encoded genes and their clinical manifestations show a great heterogeneity in terms of age of onset and severity, suggesting that patient-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 52 publications
3
36
0
Order By: Relevance
“…Consistent with its localization associated with ER–mitochondria contact sites, FATE1 expression in H295R/TR N‐Flag FATE1 cells following Dox treatment had the effect of decreasing ER–mitochondria contacts compared to control cells, as shown by a decreased overlap of signals from ER and mitochondria fluorescent probes (Fig A) and by decreased signal of a novel split‐GFP‐based probe (Fig B). Using transmission electron microscopy (TEM), we could confirm that both the number of ER–mitochondria contacts and the number of mitochondria displaying ER contact sites were reduced in Dox‐treated H295R/TR N‐Flag FATE1 compared to control cells (Fig C).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…Consistent with its localization associated with ER–mitochondria contact sites, FATE1 expression in H295R/TR N‐Flag FATE1 cells following Dox treatment had the effect of decreasing ER–mitochondria contacts compared to control cells, as shown by a decreased overlap of signals from ER and mitochondria fluorescent probes (Fig A) and by decreased signal of a novel split‐GFP‐based probe (Fig B). Using transmission electron microscopy (TEM), we could confirm that both the number of ER–mitochondria contacts and the number of mitochondria displaying ER contact sites were reduced in Dox‐treated H295R/TR N‐Flag FATE1 compared to control cells (Fig C).…”
Section: Resultssupporting
confidence: 64%
“…Scale bars, 10 μm. Effect of FATE1 expression on ER–mitochondria distance in H295R/TR N‐Flag FATE1 cells measured using a split‐GFP probe . Quantification is shown in the graph.…”
Section: Resultsmentioning
confidence: 99%
“…Previously published data showed increased mitophagy in patients with complex I deficient mtDNA disease. 5 We also have additional data supporting the same effect in fibroblasts from other classical mitochondrial optic neuropathies caused by the m.11778A>G (n = 2) and m.3460G>A (n = 1) mtDNA mutations and from a patient who is a compound heterozygote for pathogenic ACAD9 mutations (figure e-5). In the absence of an overt mitochondrial respiratory chain defect, documenting increased mitophagy in fibroblasts could be a useful functional assay that would further support the pathogenic nature of a specific mtDNA variant.…”
Section: Discussionsupporting
confidence: 55%
“…Surprisingly, our data showed decreased levels of free calcium, both in mitochondria and in cytoplasm, after the addition of the Aβ peptides. A previous study showed decreased levels of mitochondrial Ca 2+ under pathological conditions (Granatiero et al., 2015). Discordant results have been reported regarding the effects of Aβ on cellular and mitochondrial calcium, with studies showing data both consistent and contradictory with our findings (Abramov, Canevari & Duchen, 2003, 2004).…”
Section: Discussionmentioning
confidence: 99%